Το αρχείο των Εκπαιδευτηρίων Αγλαΐας Σχινά - Βαλσαμίδης, Πασχάλης (Μακεδονικά, 2011)
One of the most important educational institutions in Thessaloniki is thatof Stephanos Noukas and Aglaia Schina. The offer of the institutions to thesociety of Thessaloniki, but also of the wider Macedonia, was of innumerablevalue. From these schools graduated female students, who distinguished intothe society, educated people who occupied various positions.The record of the institutions is kept in the Society for MacedonianStudies. It includes a record of the proceedings of conferences, book of receipts and expenses, documents of the curriculum, the fees the students paid,certificates of study, scale of payments, as well as records that contain the mailof the schools, the personal mail of Aglaia Schina, etc. There are also keptphotographs, cards of thanking, postcards, medals, etc.The records were divided into eight parts. The first part includes thecodes, which come up to 49. The numbering of the codes 1-49 was applied according to the chronological order. From the sum of the 49 codes the 3 areundated. The oldest code dates back to 1907 and the last one in 1958. The first11 codes were conducted during the Ottoman Empire that is till the liberationof Thessaloniki in 1956. The second part presents documents, which were distributed according to their theme and their chronological order, for examplespeeches/demonstrations, newsletters, teachers’ nominations, correspondence,etc. It is comprised by 7 folders. The third part includes a manuscript journalof an excursion and two books with printing patterns, while the fourth one hasphotographs of the Educational Institutions of Aglaia Schina. The fifth part includes thanking cards sent to Aglaia Schina by friends and students as well aspostcards by various places in Greece. The sixth part presents frames – photographs, for example by Aglaia Schina, the composer Aimilios Riadis, etc. Theseventh part includes medals / trophies with which Aglaia Schina was awardedwith, as well as the Institution and her students. The last part presents theseals that where saved and were used by the institutions. The study closeswith the appendix, which includes photographs and documents of the institutions.